Guidelines for process equipment reliability data with data tables. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1989)
The book supplements Guidelines for Chemical Process Quantitative Risk Analysis by providing the failure rate data needed to perform a chemical process quantitative risk analysis.
Keywords: Chemical plants -- Equipment and supplies -- Reliability.; elektronické knihy; electronic books